Изменчивость числа хромосом как фактор микроэволюции и адаптации хвойных - Седельникова, Т.С. (Фактори експериментальної еволюції організмів, 2016)
Aim. Analysis of investigations of chromosome numbers in populations of coniferous species in wide range of their growing conditions are presented. Methods. Chromosome numbers studied in metaphase cells with a complete set of chromosomes in root tip meristems. Results. Study of chromosome numbers in populations of conifers from Pinaceae (10 species and 1 interspecific hybrid) and Cupressaceae (4 species) families growing under optimal conditions and from ecotopes with different level of extremality. Seed material were collected in the territory of Russia, Ukraine, Bulgaria, Czech Republic, Kazakhstan. Conclusions. There is some trend manifested in availability of mixoploidy, aneuploidy, an increasing of variability degree of chromosome numbers, presence of B chromosomes in seed progeny of conifers according to the strengthening of extreme temperature and edaphic conditions of their habitat – in the ecological limits of species propagation, with increasing altitudinal zones, on the southern and northern boundaries of the areas inside and outside, in the areas of human influence and at introductions. Keywords: chromosome numbers, coniferous species, extreme conditions.